Histological specificity of alterations and expression of KIT and KITLG in non‐small cell lung carcinoma. Issue 11 (10th September 2013) - Salomonsson, Annette; Jönsson, Mats; Isaksson, Sofi; Karlsson, Anna; Jönsson, Per; Gaber, Alexander; Bendahl, Pär‐Ola; Johansson, Leif; Brunnström, Hans; Jirström, Karin; Borg, Åke; Staaf, Johan; et al.
<x xml:space="preserve">Abstract</x> Characterization of molecules within important oncogenetic pathways may have future implications for development of therapies and biomarkers in lung cancer. One such target is the tyrosine kinase receptor KIT (c‐KIT). We evaluated alterations and expression of KIT and its ligand, KITLG (also known as SCF), in 72 clinical lung tumor specimens of different histologies. Gene copy number, mRNA expression levels, and protein expression were assayed using array‐based comparative genomic hybridization, real‐time quantitative reverse transcription PCR and immunohistochemistry, respectively. For validation, we investigated copy number alterations and mRNA expression in external microarray data sets of 1, 600 and 555 primary lung tumors, respectively. Positivity for KIT staining was most common in large cell neuroendocrine carcinoma (LCNEC) which also showed the highest KIT mRNA expression levels whereas expression was lowest in squamous cell carcinoma (SqCC). KIT mRNA expression levels were higher in KIT immunopositive samples, but expression was not affected by KIT copy numbers. Copy number gains of KIT were significantly more frequent in SqCC compared with adenocarcinoma in our own series and in the 1, 600‐sample data set. Immunopositivity for both KIT and KITLG in the same tumor was rare except in LCNEC. Our results highlight an increased KIT mRNA expression and frequent KIT immunopositivity in LCNEC but point out a poor correlation between KIT copy numbers and expression in SqCC, perhaps reflecting the existence of a protective mechanism against KIT alterations in this subgroup. © 2013 Wiley Periodicals, Inc.